A randomized trial assessing the impact of three different glycoprotein IIb/IIIa antagonists on glycoprotein IIb/IIIa platelet receptor inhibition and clinical endpoints in patients with acute coronary syndromes. Issue 5 (October 2016) - Holmes, Lewis E.; Gupta, Rohan; Rajendran, Saissan; Luu, John; French, John K.; Juergens, Craig P.
Summary: Aims: To compare three glycoprotein IIb/IIIa receptor antagonists (GPIs) in terms of platelet inhibition and major adverse cardiac events (MACEs), and assess the rate of bleeding and MACEs between GPIs and coadministered P2Y12 agents. Methods: Eighty‐three acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI) with planned GPI use were randomized to receive high‐dose bolus tirofiban, double‐bolus eptifibatide, or abciximab followed by a 12‐hour infusion. Glycoprotein IIb/IIIa platelet receptor inhibition was measured at baseline and at 10 minutes, 1 hour, and 24 hours postbolus dose. Major adverse cardiac events and bleeding complications at 30 days were documented. The incidence of MACEs and bleeding in patients receiving ticagrelor or prasugrel were compared to those given clopidogrel. Results: There were no statistically significant differences in platelet inhibition between GPIs at 10 minutes ( P =.085) and 1 hour ( P =.337). At 24 hours, abciximab achieved statistically significantly higher median [interquartile range] platelet inhibition (75 [65–88]%) compared to tirofiban (28 [3–56]%; P <.0001) and eptifibatide (44 [31–63]%; P =.007). There were no differences in bleeding or MACEs depending on GPI or P2Y12 inhibitor administered. Conclusions: Glycoprotein receptor inhibitors achieve similar levels of platelet inhibition at 10 minutes and 1 hour; however, abciximab maintains this benefit 24 hours after bolus dose. We did not witness an increased rate of bleeding in patients given new potent P2Y12 inhibitors and a GPI in the modern era.